THE SREBRENICA MASSACRE OF 1995 IS THE BIGGEST TRIUMPH OF PROPAGANDA (Heritage, 2021)
There was no genocide against the Muslim population in Srebrenica in July 1995 because genocide did not occur. Crimes were committed in Srebrenica. The Republika Srpska Army did not intend to commit genocide. Searching in their research, the authors could not find a single statement by Republika Srpska officials who, before the war, during the war or during Operation Srebrenica, stated that they wanted to destroy the Muslim population, their language or script or cultural and religious monuments. During the liberation of Srebrenica, the Republika Srpska Army passed through 42 Muslim villages and did not leave behind a single killed civilian, woman, child or wounded. That was the biggest surprise for the directors of the war and Srebrenica.  Furthermore, the Army of the Republika Srpska had no plan to destroy the Muslim population or capture Srebrenica, it just wanted to reduce the enclave to Srebrenica. The crime in Srebrenica was prepared by Bill Clinton, Alija Izetbegović and Franjo Tuđman. Clinton told Izetbegović that at least 5,000 Muslims must be killed for NATO to bomb Serbs. That is why the Muslim population and Muslim forces were sacrificed. Alija Izetbegović and Bill Clinton played a game about the number of crimes in Srebrenica. They needed a large number of victims, because the United States and the Croats agreed to expel 250,000 Serbs from Krajina in the criminal action "Storm". In order not to talk about the ethnic cleansing of Serbs from Krajina and Croatia, they needed Srebrenica victims to talk about them.  That is why they needed the number of over 5,000 Muslim victims. There were no children or women among the Muslim victims found, and they are the key to reproduction. This means that the Serbs did not intend to destroy the Muslim population, which is another proof that there was no genocide in Srebrenica. Based on relevant witnesses of foreign provenance, as well as relevant sources, both domestic and foreign, starting from the definition of genocide, the authors came to the conclusion that there was no genocide in Srebrenica. Genocide never happened. A major crime occurred, after 3,000 Serbs were killed in and around Srebrenica and 200 Serb villages burned. And because of that, the United States, Franjo Tudjman and Alija Izetbegović needed Srebrenica in order not to talk about Serb victims, but about Srebrenica victims.
Keywords: Srebrenica, propaganda, victims, Muslims, bombing of Serbia